Hymenaea parvifolia Huber: dormancy breaking, morphology of fruit, seed and seedling - Domingues Ribeiro, Olívia; Cruz, Eniel David; Falcão da Silva, Mônica; de Aviz Chaves, Betânia; Domingues Ribeiro, Olinda Maria; Cajueiro Gurgel, Ely Simone (Revista Ceres, 2025)
The successful use of native species in conservation actions depends on basic knowledge of their biology, beginning with the identification of regenerating individuals in the field, up to the behavior and development of the species from the early stages of germination. Moreover, seed propagation and germination may be limited by the occurrence of dormancy. The objective of this work was to identify the best method to overcome seed dormancy of Hymenaea parvifolia Huber, besides characterizing the fruits, seeds, post-seminal development and seedlings of naturally occurring specimens in Amazonia. For this, (i) tests for the breakdown of dormancy were performed through thermal, chemical and mechanical treatments; (ii) analyses of their effects on seed germination were made; and (iii) morphology of germinative development of Hymenaea parvifolia was described. The treatments based on sulfuric acid for 15, 25 and 35 minutes were the most efficient in overcoming the integumentary dormancy. However, scarification by grinding is recommended because it had been less impact on the environment. External characteristics and shape of the fruit, seed and epicotyl can aid taxonomy of the genus and identification of its species in the field. In addition, morphological characters of the fruit, seed, germination and seedling were illustrated.